FAKTOR PENDORONG TERGABUNGNYA REMAJA DALAM KELOMPOK SOSIAL PERTEMANAN: STUDI ATRAKSI INTERPERSONAL PADA GENG PLECING CREW (PLC) SMAN 2 DENPASAR - Vinenda, Ayu Nyoman; Suryawati, IGA Alit; Purnawan, Ni Luh Ramaswati (E-Jurnal Medium; Vol 1 No 1 (2016), 2016)
ABSTRACT The group of  Plecing Crew (PLC) is one of the big groupsand it is a famous in SMAN 2 Denpasar. Though it is  a new-established group, but it has more than 1300 members ranging from the 1 st batch up to now the 7 th . This could be happened because most members always take part in any events conducted by the school and the group itself. The idea of creating this group is to unite all the students of the same batch to stand against the arrogance of the seniors. To analyze the factors that influence the interest of the students to join the social group of friendship, this research applies Jalaluddin Rakhmat’s concepts on interpersonal attraction factors, Irwin Altman’s and Dalmas Taylor’s theory of social penetration, and the theory of social exchange developed by two psychologist John Thibaut and Harlod Kelley (1959), and two sociologist George Homans (1974) also Lott and Lott (1974).The method of this research is qualitative-descriptive by spreading the semi-structured interview to collect the data. The finding of the research shows that the factors to influence the interest of the students to join the social group of  friendship are in accordance with the Jalaluddin Rakhmat’s concepts on interpersonal attraction, they are the similar personal characteristics, stress, social isolation, physical attraction, reward, familiarity, and closeness. Key Words: Interpersonal Attractions Factors, Social Group of Friendship, Group of Plecing Crew (PLC), SMAN 2 Denpasar.